Prevalence of Internet Gaming Disorder and Its Association With Personality Traits and Gaming Characteristics Among Chinese Adolescent Gamers - Liao, Zhenjiang; Huang, Qiuping; Huang, Shucai; Tan, Linxiang; Shao, Tianli; Fang, Ting; Chen, Xinxin; Lin, Shuhong; Qi, Jing; Cai, Yi; Shen, Hongxian (Frontiers in Psychiatry, 2020)
Background: Internet gaming is extremely popular in China. However, some players overuse it, with negative outcomes. Knowing the prevalence rate and specific risk factors can provide a better understanding of the etiology of Internet Gaming Disorder (IGD). This study aimed to estimate the prevalence of IGD among Chinese adolescents and its association with their personality traits and Internet gaming characteristics. Methods: A cross-sectional study design was utilized in this study. Participants were recruited from 34 provincial administrative districts in China and consisted of 6,379 adolescent game players aged 15–25 (males/females = 3,701/2,678, mean age: 19.35 ± 1.61). A self-report structured questionnaire containing questions regarding demographic information and Internet gaming use characteristics, the Video Gaming Dependency Scale, and the Chinese Big Five Inventory-brief version, was used in the study. Results: The prevalence of IGD among Chinese adolescent game players was 17.0%. All participants were divided into the IGD group (males/females = 751/333, mean age: 19.74 ± 1.85) or the non-IGD group (males/females = 2,950/2,345, mean age: 19.27 ± 1.54). Specifically, twelve factors were significantly associated with IGD (p < 0.001), including neuroticism (β = 0.17), conscientiousness (β = −0.14), Internet gaming time per day (Hour) (β = 0.21), Internet gaming charge per month (Yuan) (β = 0.21), motive: escaping (β = 0.15), motive: sensation seeking (β = 0.13), motive: maintaining (β = 0.08), motive: coping (β = 0.06), having one or two long-term game partners (β = 0.06), male (β = 0.12), undergraduate and above (β = 0.04), and relationship status of couple (β = 0.04). Conclusion: Our findings offer evidence with respect to the prevalence of IGD and its relationships with specific personality traits and Internet gaming characteristics in China. It is necessary for Chinese parents, teachers, and social workers to pay more attention to adolescents' personality traits of high neuroticism and low conscientiousness, long time and high expense they spend on game, as well as their motives.